Post-magmatic processes recorded in bimodal chromitites of the East Chalkidiki meta-ultramafic bodies, Gomati and Nea Roda, Northern Greece - Sideridis, Alkiviadis; Tsikouras, Basilios; Tsitsanis, Pavlos; Koutsovitis, Petros; Zaccarini, Federica; Hauzenberger, Christoph; Tsikos, Harilaos; Hatzipanagiotou, Konstantin (Frontiers in Earth Science, 2022)
The meta-ultramafic bodies of Gomati and Nea Roda are situated in the Serbomacedonian Massif. They demonstrate bimodal character in terms of chromitite chemistry with both Cr- and Al-rich chromitites outcropping in proximity, with no obvious tectonic structure intercepting those two varieties. Based on the trace element abundances in spinel grains, metamorphosis reached amphibolite facies, forming porous spinel. Chromitite-hosted chlorite and garnet chemistry correlates with greenschist facies temperatures and formation of zoned spinel grains. Despite the metamorphic overprint, some of the primary features of the chromitites have been preserved. The PGE contents demonstrate an increase in Pd/Ir ratios in some chromitites pointing to fractionation, whereas low ratios of mostly Cr-rich chromitites point to partial melting being the main mechanism that controls PGE mineralization. The normalized trace element patterns of spinel-group minerals revealed that Al-rich chromitites were generated in spreading settings in a back-arc and the Cr-rich counterparts in SSZ environment. The parental melts of Al-rich and Cr-rich chromitites demonstrate MORB and boninitic affinities, respectively. The meta-ultramafic protoliths were modified within a subduction zone, with significant input of a sedimentary source, as confirmed by the chemistry of serpentinite, diopside and Sb-mineralization. These results suggest common geotectonic processes within the Rhodope and the Serbomacedonian massif, that have affected the ultramafic bodies and chromitite occurrences.